Residual internal limiting membrane in epiretinal membrane surgery. Issue 8 (11th February 2009) - Kifuku, K; Hata, Y; Kohno, R-i; Kawahara, S; Mochizuki, Y; Enaida, H; Sonoda, K-h; Ishibashi, T
Abstract : Background/aim: To examine the degree of the residual internal limiting membrane (ILM) after epiretinal membrane (ERM) peeling. Methods: Sixty-one eyes of 59 patients with ERM were enrolled. After ERM peeling, residual ILM was visualised with Brilliant Blue G (BBG). The residual ILM pattern was divided into three groups: (1) residual type (ILM mostly remained), (2) half type (approximately half of ILM remaind), (3) no residual type (ILM mostly removed with ERM). If ILM remained, residual ILM was removed in all cases and histologically examined using the flat mount method in 10 cases. The correlation between the degree of ERM evaluated by preoperative best-corrected visual acuity (BCVA) and residual ILM pattern was also examined. Results: Twenty-eight eyes (45.9%) were of the residual type. Three eyes (4.9%) were of the half type, and 30 eyes (49.2%) were of no residual type. The mean preoperative BCVA showed no significant correlation with the residual ILM pattern. Flat mount immunohistochemistry revealed many remnant cells, both glial fibrillar acidic protein positive and negative, on residual ILMs in all specimens examined. No recurrence that needed surgical treatment was observed. Conclusion: Residual ILM with remnant cells seems to be frequent after ERM removal. Intraoperative staining with BBG may be helpful in determining the extent of ILM removal.